2022
DOI: 10.3389/fdgth.2022.951366
|View full text |Cite
|
Sign up to set email alerts
|

Digital competency of Psychologists in Aotearoa New Zealand: A cross-sectional survey

Abstract: BackgroundThe increasing implementation of digital health into psychological practice is transforming mental health services. Limited clinical resources and the high demand for psychological services, alongside the restrictions imposed on services during the global COVID-19 pandemic, have been a catalyst for significant changes in the way psychologists work. Ensuring Psychologists have the skills and competence to use these tools in practice is essential to safe and ethical practice.AimThis study aimed to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As previous studies, and our earlier surveys, have highlighted, the support for the secondary use of health information is conditional. [ 5 – 7 , 15 ] Key conditions for patient support of secondary use of health information include the use being for the greater good and that they can trust their health service (or those who collected the data) to protect and care for their health information. Not only is it paramount that the secondary use of health information is for the direct purpose of benefiting others, but there also needs to be assurances that its use will not result in immediate or secondary harm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous studies, and our earlier surveys, have highlighted, the support for the secondary use of health information is conditional. [ 5 – 7 , 15 ] Key conditions for patient support of secondary use of health information include the use being for the greater good and that they can trust their health service (or those who collected the data) to protect and care for their health information. Not only is it paramount that the secondary use of health information is for the direct purpose of benefiting others, but there also needs to be assurances that its use will not result in immediate or secondary harm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in NZ has shown that both patients and the general public are largely comfortable with the secondary use of their de-identified health information. [ 6 , 15 ] A survey of 1,377 current patients found that over 80% were comfortable with their health information being used across a range of scenarios. Comfort with the use of individual health information was related to assurances that its use was for public good, data was stored securely, individual privacy was maintained, and there was communication on how it was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivational barriers can also appear in the three hypothesis relations of interest, especially from a psychological perspective, since the users may not feel able to use the digital tools. This can occur as a result of their socioeconomic level or personal learning difficulties, which may make it difficult to absorb the necessary experience needed to use these tools productively (Dobson et al 2022). There is another perspective for these difficulties in adopting digital work and competences; cognitive difficulties, related to neurological disorders, can disable workers.…”
Section: The Negative Effects Of Digital Competence Over Innovative W...mentioning
confidence: 99%